Gambaran Disfungsi Seksual pada Pasien Diabetes Melitus Tipe II di Poli Penyakit dalam RSUD Mardi Waluyo Kota Blitar - Sukma Puji Rahayu; Tri Cahyo Sepdianto; Arif Mulyadi (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Chronic complications of diabetes mellitus was the most common autonomic neuropathy resulted in sexual dysfunction. The aim of research was to described the sexual dysfunction in patients with type 2 diabetes mellitus at Poli Penyakit Dalam Mardi Waluyo Hospital Blitar. The research method used descriptive design. The population in this study were patients with type 2 diabetes mellitus who visited in poli penyakit dalam in Mardi Waluyo Hospital Blitar in April as many as 856 people, and a sample of 86 people were taken using purposive sampling technique. Collecting data used the FSFI questionnaire for womens and IIEF for mens. These results indicate that the majority of patients with type 2 diabetes mellitus sexual dysfunction. In patients 75% of women experience sexual dysfunction. At 74% of men with erectile dysfunction, 88% experienced orgasm dysfunction, 85% experienced sexual desire dysfunction, 86% experienced a satisfying sexual dysfunction, 89% overall satisfaction dysfunction. The suggestion in this research was expected FSFI and IIEF questionnaire could be used as a tool to monitor the presence of sexual dysfunction in Blitar.